Enhancing Competence and BNS Certification for Loading Master and Draught Survey to Realize Professional and Competitive Maritime Human Resources - Hadiansyah Hadiansyah (Siber Nusantara of Community Service Review, 2025)
The maritime sector demands high accuracy and professionalism in cargo handling operations to minimize financial losses due to cargo discrepancies. This community service activity aims to enhance the competence of maritime human resources through technical training and BNSP (National Professional Certification Agency) certification in the Loading Master and Draught Survey schemes. The implementation method involved intensive mentoring, including maritime regulation theory, hydrostatic table calculation simulations, and official competency assessments by the Professional Certification Body (LSP). The results indicate that the integration of technical expertise (ship draught calculations) and formal BNSP certification significantly increases the confidence and bargaining power of practitioners in the logistics industry. By strengthening these competencies, it is expected to create a maritime work ecosystem that is more accurate, transparent, and internationally competitive.